The craft of scene writing eaudiobook Beat by beat to a better script. - Mercurio, Jim (Tantor Media, 2020)
A professional screenwriter's master class in writing the most critical and challenging script element—the individual scene. No one comes out of a movie talking about structure. What audiences love and remember about a movie are great scenes. Marlon Brando in the back seat in On the Waterfront giving his "I could'a been a contender" speech. Meg Ryan's fake orgasm in Katz's Deli in When Harry Met Sally with the climactic punch line: "I'll have what she's having." In Superbad , Jonah Hill professing "I love you" to his friend Michael Cera by touching his nose with a "boop." Great scenes will elevate your script from ho-hum to extraordinary—and from the slush pile to sellable. In The Craft of Scene Writing , accomplished screenwriter and master writing teacher Jim Mercurio analyzes and systematizes the beats, conflicts, character moments, action, dialogue, and structure that create powerful scenes. Citing examples from scripts old and new, The Craft of Scene Writing breaks down how great scenes reveal character, advance the story, and emotionally connect with audiences, plus demonstrates how to use these techniques in your own scripts. This incredibly detailed exploration of screenwriting technique will help beginning writers to write great scripts and experienced writers to gain a more complete mastery of their craft.